Analisis Self-Confidence pada Siswa Kelas VII SMP dalam Pembelajaran Matematika - Amrullah, Azman Shidiq; Hanifah (Papanda, 2025)
The aim of this study is to analyze the level of self-confidence among seventh-grade students in mathematics learning at SMP Negeri 3 Klari. Self-confidence is one of the important affective aspects that contributes to student success, especially in mathematics, which is often perceived as a difficult subject. This research employed a qualitative approach with a descriptive method. The sampling technique used was purposive sampling, resulting in a total of 30 students as respondents. The instrument used was a Likert scale questionnaire, validated by two experts. Data were analyzed using percentage calculations and attitude scale interpretation. The results showed that the average level of students’ self-confidence fell into the more than half category, with an overall percentage of 63.76%. These findings indicate that while most students have demonstrated a moderate level of self-confidence in learning mathematics, more effective and supportive instructional strategies are still needed to enhance students’ belief in their own abilities.